Systemic effects of whole-body cooling to 35°C, 33.5°C and 30°C in a piglet perinatal asphyxia model: implications for therapeutic hypothermia - Kerenyi, Aron (Pediatr Res, 2012)
The precise temperature for optimal neuroprotection in infants with neonatal encephalopathy is unclear. Our aim was to assess systemic effects of whole-body cooling to 35°C, 33.5°C and 30°C in a piglet perinatal asphyxia model. Twenty-eight anesthetised male piglets aged <24h underwent hypoxia-ischemia and randomized to normothermia; or cooling to rectal temperature (Trec) 35°C, 33.5°C, or 30°C during 2-26 h post insult (groups n=7). Heart rate (HR), mean arterial blood pressure (MABP) and Trec were recorded continuously. Five 30°C animals had fatal cardiac arrests. During 30°C cooling HR was lower vs normothermia (p<0.001). Although MABP did not vary between groups, more fluid boluses were needed at 30°C than normothermia (p<0.02); dopamine use was higher at 30°C than normothermia and 35°C (p=0.005, p=0.02). Base deficit was increased at 30°C at 12,24 and 36h vs all other groups (p<0.05), pH was acidotic at 36h vs normothermia (p=0.04) and blood glucose higher for 30°C at 12h vs normothermia and 35°C (p<0.05). Potassium was lower at 12h in the 30°C group vs 33.5°C and 35°C groups. Cortisol was no different between groups. Cooling to 30°C led to metabolic derangement, more cardiac arrests and deaths than cooling to 33.5°C or 35°C. Inadvertent overcooling should be avoided.